The Fox as a Dying Hero: An Edition and Translation of the Late Medieval Icelandic Poem Skaufalabálkur - Þorgeirsson, Haukur; Sayers, William (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2023)
The late-medieval Icelandic poem Skaufalabálkur describes the final hunting trip of an old fox in a style mimicking heroic epic. The work is traditionally connected with poets working at or near Skarð in Western-Iceland in the 15th century and we argue here that the language of the poem is consistent with that dating. This new edition presents a text of the poem based on the oldest manuscript with some advances in the reading and interpretation of certain words. The translation aims to accurately transmit the poem’s rich vocabulary pertaining to the life of foxes and medieval farming in the subarctic and to accessibly convey a satiric gem to a modern audience.